"n Gemeenskapsgerigte model vir die geloofsvorming van tieners in die verbondsgesin deur middel van simbole en rituele - Wet, D. C. de (HTS teologiese studies, 2003)
A community-directed model for the faith development of teenagers in the covenantal family by means of sym-bols and ritualsThe covenantal family is the most important building system in the church and the society. Almost all families live in a community where interactions of faith take place. Teenagers leave the church because this community does not offer enough exciting activities for them to be part of a transformation process for a better life. For this reason we need an event-driven and a community-directed teenage and family ministry that accentuates processes, people and relations. Better relationships within the congregation and community needs better communication through symbols and rituals. This paradigm needs an exegesis of the Bible, the culture, the self and the community. Strengthening the inner life of churches and their relation with their immediate communities should be the first priority of church leaders.